Elephants swim - Riley, Linda Capus; Jenkins, Steve, 1952- (Boston : Houghton Mifflin, 1995)
Describes in rhyme how various animals such as elephants, kangaroos, armadillos, and caribou behave in water.
Elem. School Library Collection
School Library Journal
Wilson's Children
2.6
K-3
K-3
Keywords: Swimming -- Juvenile literature; Animal swimming; Animals; Swimming